Students’ part-time work: an implication towards students’ academic performance / Nor Khairunnisa Mat Yunus ... [et al.] - Mat Yunus, Nor Khairunnisa; Awang Kader, Mohd Aidil Riduan; Ali, Roslina; Mohamed Badri, Shamsul Nizam (2014)
This paper reports on the subject of higher education institution students undertake paid part time work while studying. A quantitative survey conducted among students of higher education institution in Pahang investigated several aspects of motives students to engage in part time work and their implication towards student academic performance. Structural Equation Modeling (SEM) has been used as statistical technique to test and estimate causal relationship between variable. The results provide an insight into the nature of work profile involves and the students’ perceptions of paid part time work. The findings raise issues which are interest to academic and non-academic staff, students, employers and higher education institutions.